Facebook Live as a new way to consume news. An approach to the Peruvian digital user - Albornoz Falcón, Carolina Leonor (2020)
Since it’s expansion in 2006, Facebook has revolutionized not only how people communicate each other but also how they get informed. Through Facebook Live -a real-time video playback tool- users can access multimedia information and participate in it in the interactive way. This platform is the object of study of this research. Through the content analysis of the Facebook Live transmissions of daily newspaper La República and El Comercio, in their digital versions; and RPP news radio station, we discovered how this tool has changed the way the Peruvian digital users get informed; and also,  how they consume the news through Facebook Live and how the characteristics of the new media as media convergence, articulating hypertext and participatory culture are present in the Facebook Live transmissions which were analyzed for the purposes of this study.